Sleep disturbances and risk of sports injury among collegiate student-athletes - Messman, B. A.; Petrie, K. A.; Moore, E. W. G.; Petrie, T. A. (Clinical Journal of Sport Medicine, 2025)
Objective: The purpose of this study was to examine the relationship between collegiate student-athletes` sleep and injury status.